The Absentee Minister of Education of Canada: The Canadian federal government’s constitutional role in First Nations education - Phillips, Ron (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2011)
In Canada, education is generally referred to as being the exclusive constitutional responsibility of the provinces and territories. However, the federal government has a constitutional responsibility. This responsibility comes from the Constitution Act 1982 and Treaties 1 - 11 between the Crown (i.e., The Government of Canada) and First Nations throughout Canada. It is very difficult to find any mention of the federal government’s constitutional education responsibilities in the literature or documents. This has allowed the federal government to downplay their educational responsibilities throughout Canada and the world. This paper examines the federal government’s constitutional responsibilities in First Nations education and makes recommendations.